2017
DOI: 10.1108/jmd-09-2016-0166
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cross-cultural training on expatriates’ adjustment

Abstract: Purpose One of the most important issues multinational corporations (MNCs) face in their global operations is expatriate failure. It is estimated that between 10 and 80 percent of expatriates sent on overseas assignments return home early. The purpose of this paper is to investigate the impact of cross-cultural training (CCT) on different facets of expatriate managers’ adjustment in Nigeria. Design/methodology/approach A sample of 212 western expatriate managers working in Nigeria was surveyed. Respondents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
(33 reference statements)
5
13
0
Order By: Relevance
“…Overall, our results are consistent with previous findings that show cross‐cultural understanding, language proficiency, and previous overseas experience affect the level of psychological comfort with general living conditions, interactions with local people, and the new workplace (Hechanova et al, 2003; Okpara & Kabongo, 2011, 2017; Peltokorpi, 2008; Puck et al, 2008; Selmer, 1999, 2002a, 2002b; Selmer et al, 1998; Tarique & Caligiuri, 2009; Waxin & Panaccio, 2005; Wurtz, 2014). We also found that postarrival CCT seems to influence expatriate adjustment slightly more than predeparture CCT.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Overall, our results are consistent with previous findings that show cross‐cultural understanding, language proficiency, and previous overseas experience affect the level of psychological comfort with general living conditions, interactions with local people, and the new workplace (Hechanova et al, 2003; Okpara & Kabongo, 2011, 2017; Peltokorpi, 2008; Puck et al, 2008; Selmer, 1999, 2002a, 2002b; Selmer et al, 1998; Tarique & Caligiuri, 2009; Waxin & Panaccio, 2005; Wurtz, 2014). We also found that postarrival CCT seems to influence expatriate adjustment slightly more than predeparture CCT.…”
Section: Discussionsupporting
confidence: 92%
“…An item analysis of our questionnaire reveals that postarrival CCT contributes most to general, work, and interaction adjustment. Our findings are in line with prior studies (Aravind et al, 2017; Martins & Tomé, 2015; Okpara & Kabongo, 2011, 2017; Selmer, 2001a, 2001b; Wang & Tran, 2012), which confirms that cross‐cultural predeparture and postarrival training programs help expatriates successfully adjust to their new environment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations